1970
DOI: 10.3329/ptcb.v18i1.3267
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in Hexaploid and Tetraploid Wheat Genotypes Using Microsatellite Markers

Abstract: The genetic diversity of a set of hexaploid and tetraploid wheat germplasm at the IPK gene bank, Gatersleben, Germany was investigated by applying 13 wheat microsatellites (WMS). The materials consisted of 63 accessions of Triticum aestivum, T. dicoccon and T. durum obtained from different collection missions. In total, 126 alleles were detected with an average of 9.7 alleles per locus. The average PIC values per locus varied from 0.65 for the marker Xgwm192 to 0.88 for the marker Xgwm619. All the primer pairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…The PIC values recorded in this study are significantly higher than the PIC values reported in the other studies of Roder et al (1995) and Plaschke et al (1995). Uddin and Boerner (2008) also found similar observations of high PIC. The markers showed an average relatively high PICvalues which confirm that SSR markers used in this Fig.…”
Section: Molecular Screening For Drought Tolerance Wheat Genotypessupporting
confidence: 81%
“…The PIC values recorded in this study are significantly higher than the PIC values reported in the other studies of Roder et al (1995) and Plaschke et al (1995). Uddin and Boerner (2008) also found similar observations of high PIC. The markers showed an average relatively high PICvalues which confirm that SSR markers used in this Fig.…”
Section: Molecular Screening For Drought Tolerance Wheat Genotypessupporting
confidence: 81%
“…The model-based population structure analysis is one of the choicest tools for the genetic categorization of any plant species including the perennial fruit tree species [ 86 ], which could be successfully utilized in conservation and optimization of the collected germplasm [ 87 ]. In the recent past, model-based population structure analysis was used for genetic differentiation of the guava germplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity analysis of wheat landraces might permit to precise their classification and confirm their origin. The estimated genetic diversity of wheat landraces has great importance for optimal utilization of germplasm for plant breeding and other activities [9]. So, it is necessary to study the genetic diversity in wheat landraces in order to broaden the genetic variation of available germplasm for future breeding and conservation programs [10].…”
Section: Discussionmentioning
confidence: 99%